2019
DOI: 10.1002/pi.5860
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and ionic conductivity relationship in silk/cellulose biocomposites

Abstract: The relationship between morphology and the ionic conductivity of polysaccharide–protein bio‐electrolyte membranes is explored in this study. Structural proteins and polysaccharides form hydrophobic and electrostatic interactions, and the resulting matrices can exhibit novel and useful properties. However, transforming these natural biomacromolecules from their native state to a more usable form is challenging. The structural, morphological, thermal, mechanical and electrical properties of biomaterials compose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 44 publications
(74 reference statements)
3
29
0
Order By: Relevance
“…It was also observed that most of the morphology changes occurred as a function of anion type in ionic liquids. In one study [25], a 10:90 ratio of B. Mori silk-cellulose films was investigated as a function of ionic liquid type. Six types of ionic liquids were used in this study, including AMIMCl, BMIMCl, EMIMCl, EMIMAc, 1-Butyl-3-methylimidazolium bromide (BMIMBr) and 1-Butyl-3methylimidazolium methane sulfonate (BMIMMeSO3).…”
Section: Ionic Liquid Abbreviation(s)mentioning
confidence: 99%
See 2 more Smart Citations
“…It was also observed that most of the morphology changes occurred as a function of anion type in ionic liquids. In one study [25], a 10:90 ratio of B. Mori silk-cellulose films was investigated as a function of ionic liquid type. Six types of ionic liquids were used in this study, including AMIMCl, BMIMCl, EMIMCl, EMIMAc, 1-Butyl-3-methylimidazolium bromide (BMIMBr) and 1-Butyl-3methylimidazolium methane sulfonate (BMIMMeSO3).…”
Section: Ionic Liquid Abbreviation(s)mentioning
confidence: 99%
“…This is because the biopolymers are separated due to their electrostatic interactions with the anions in the ionic liquid. The removal of the solvent allows for the biopolymers to interact with each other using hydrogen bonding and causes them to aggregate into a fiber [25]. In addition to ionic liquid extraction, water also helps to modify the diameter and structure of the nanofibers.…”
Section: Watermentioning
confidence: 99%
See 1 more Smart Citation
“…Salas-de la Cruz and coworkers have investigated the morphological and conductive changes that occur as a result of using ionic liquids (EMIMCl and EMIMOAc) in the dissolution of cellulose/silk biocomposites. 5 Correlations between ionic conductivity, cellulose crystallinity and -sheet content are discussed. X-ray scattering studies showed that coagulation with hydrogen peroxide lead to a high degree of crystallinity and -sheet content which, in turn, resulted in higher ionic conductivity.…”
Section: In Focus: Poly(ionic Liquid)s In Polymer Science and Engineementioning
confidence: 99%
“…Ionic liquids have become increasingly important in the extraction and dissolution of biomacromolecules. Salas‐de la Cruz and coworkers have investigated the morphological and conductive changes that occur as a result of using ionic liquids (EMIMCl and EMIMOAc) in the dissolution of cellulose/silk biocomposites . Correlations between ionic conductivity, cellulose crystallinity and β ‐sheet content are discussed.…”
mentioning
confidence: 99%